Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1074/jbc.m116.772541
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in the activity of presynaptic γ-aminobutyric acid type B receptors contribute to altered neuronal excitability in fragile X syndrome

Abstract: The behavioral and anatomical deficits seen in fragile X syndrome (FXS) are widely believed to result from imbalances in the relative strengths of excitatory and inhibitory neurotransmission. Although modified neuronal excitability is thought to be of significance, the contribution that alterations in GABAergic inhibition play in the pathophysiology of FXS are ill defined. Slow sustained neuronal inhibition is mediated by γ-aminobutyric acid type B (GABA) receptors, which are heterodimeric G-protein-coupled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…In the mouse FXS model, recent work shows FMRP loss changes cell differentiation kinetics for both neurons and glia (Table 1) [14], and astrocyte-specific FMRP knockout in mice increases neuronal dendritic spine density similar to the global FXS condition [15]. Within neurons in all model systems, the soma contains the vast majority of FMRP, yet the lion’s share of research and discussion focuses on local FMRP functions at the synapse [2,1619]. Most study postsynaptic mechanisms, but there appears to be at least as many presynaptic mRNA targets and presynaptic defects in mutants [2,16,20,21].…”
Section: Overview Of Expanding Fmrp Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse FXS model, recent work shows FMRP loss changes cell differentiation kinetics for both neurons and glia (Table 1) [14], and astrocyte-specific FMRP knockout in mice increases neuronal dendritic spine density similar to the global FXS condition [15]. Within neurons in all model systems, the soma contains the vast majority of FMRP, yet the lion’s share of research and discussion focuses on local FMRP functions at the synapse [2,1619]. Most study postsynaptic mechanisms, but there appears to be at least as many presynaptic mRNA targets and presynaptic defects in mutants [2,16,20,21].…”
Section: Overview Of Expanding Fmrp Functionsmentioning
confidence: 99%
“…For example, a GABA b R subunit (R1a) mediating presynaptic inhibition is reduced in FMR1 knockout mice [73]. Similarly, the Drosophila FXS model shows deficits in GABA b R suppression of presynaptic glutamate release [19]. This early delay in GABA signaling is followed by later overelaboration of GABAergic neurons in a Drosophila brain learning/memory center [27].…”
Section: Part Iv: New Progress In Excitatory/inhibitory (E/i) Balancementioning
confidence: 99%
“…In some neurons FMRP has been shown to be present directly at the presynapse as well as in axon-restricted fragile X granules (FXGs), which can be observed especially during particularly plastic developmental stages (Christie et al 2009;Akins et al 2012). A presynaptic role has been suggested, as the absence of FMRP correlates with dysregulations in GABA release (Centonze et al 2008;Kang et al 2017), causing imbalances between inhibitory and excitatory neurotransmission. Additionally, several studies showed that FMRP is able to regulate presynaptic ion channel stability, trafficking, surface expression as well as sensitivity indicating a presynaptic role Strumbos et al 2010;Gross et al 2011;Lee et al 2011;Zhang et al 2012;Ferron et al 2014;Wang et al 2014;Deng & Klyachko, 2016).…”
Section: The Fragile X Syndromementioning
confidence: 99%
“…; Kang et al . ), causing imbalances between inhibitory and excitatory neurotransmission. Additionally, several studies showed that FMRP is able to regulate presynaptic ion channel stability, trafficking, surface expression as well as sensitivity indicating a presynaptic role (Brown et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that presynaptic GABA B R expression can be altered by pathophysiological conditions. For example, presynaptic GABA B R expression is reduced in fragile‐x syndrome (Kang et al ) and following seizures (Straessle, Loup, Arabadzisz, Ohning, & Fritschy, ; Thompson, Ayman, Woodhall, & Jones, ) or prolonged exposure to methamphetamine (Padgett et al, ). Presynaptic GABA B R expression is also reduced following long‐term activity blockade with tetrodotoxin (Laviv et al, ), suggesting homeostatic regulation of receptor expression.…”
Section: Introductionmentioning
confidence: 99%